1985
DOI: 10.1097/00000658-198504000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Lesions of the Common Bile Duct at Cholecystectomy

Abstract: Sixty-five cases of accidental lesion of the choledochus at cholecystectomy reported from 51 Swedish hospitals to the Patients' Insurance Syndicate in Stockholm 1975-1981 were studied. The results were evaluated as to the time of detection and the primary surgical repair done. Fifty-five of the 65 lesions were detected and repaired at the cholecystectomy and ten were detected and repaired the first 10 days after the primary operation. In 38 of 55 lesions detected before surgery, an end-to-end choledochostomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
10

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(90 citation statements)
references
References 6 publications
3
77
0
10
Order By: Relevance
“…However, it is wrong to assume that operative cholangiography always affords protection against duct damage [9,10]. The injury can occur due to poor surgical technique after the study has shown a normal biliary tree, or because the operative cholangiogram was interpreted incorrectly [11]. Bengmark et al [11] reported 65 injuries of the choledochus at cholecystectomy in patients when peroperative cholangiography was performed in all except three.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is wrong to assume that operative cholangiography always affords protection against duct damage [9,10]. The injury can occur due to poor surgical technique after the study has shown a normal biliary tree, or because the operative cholangiogram was interpreted incorrectly [11]. Bengmark et al [11] reported 65 injuries of the choledochus at cholecystectomy in patients when peroperative cholangiography was performed in all except three.…”
Section: Discussionmentioning
confidence: 99%
“…The injury can occur due to poor surgical technique after the study has shown a normal biliary tree, or because the operative cholangiogram was interpreted incorrectly [11]. Bengmark et al [11] reported 65 injuries of the choledochus at cholecystectomy in patients when peroperative cholangiography was performed in all except three. Surgeons performing cholecystectomy should be aware of the many anatomical variations which occur, especially in the Calot's triangle, and thus the need to expose the area clearly before any structures are divided, clamped, or ligated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent times, multi centre series, national surveys and single centre series have estimated that the overall prevalence of bile duct injury during the era of open cholecystectomy to be around 0.1-0.2% (10,11,12). This low incidence has occurred over a century of experience and could be considered as a reference for comparison for other techniques of cholecystectomy.…”
Section: Bile Duct Injuries During the Era Of Open Cholecystectomymentioning
confidence: 99%
“…The incidence of BDI during open cholecystectomy is reported to be approximately 0.1-0.2% [1][2][3]. The exact incidence of BDI following LC is not known, but is definitely higher than that following open cholecystectomy and reportedly varies between 0.4% and 0.6% [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%